Hydrogel-Forming Microneedles in the Management of Dermal Disorders Through a Non-Invasive Process: A Review - Popat Mohite; Abhijeet Puri; Shubham Munde; Nitin Ade; Ashwini Kumar; Pensak Jantrawut; Sudarshan Singh; Chuda Chittasupho (Gels)
Microneedle (MN) technology has emerged as a promising approach for delivering therapeutic agents to the skin, offering significant potential in treating various dermal conditions. Among these technologies, hydrogel-forming microneedles (HFMNs) represent a transformative advancement in the management of dermal diseases through non-invasive drug delivery. These innovative devices consist of micrometer-sized needles made of native or crosslinked hydrophilic polymers, capable of penetrating the stratum corneum without damaging underlying tissues. Upon insertion, HFMNs rapidly absorb interstitial fluid, swelling to form a hydrogel conduit that enables the efficient transport of therapeutic agents directly into the dermal microcirculation. The non-invasive nature of HFMNs enhances patient compliance by eliminating the pain and discomfort associated with traditional hypodermic needles. This technology allows for the delivery of a wide range of drugs, including macromolecules and biomacromolecules, which are often difficult to administer dermally due to their size and polarity. Moreover, HFMNs provide controlled and regulated release profiles, enabling sustained therapeutic effects while minimizing systemic side effects. Additionally, HFMNs can be used for both drug delivery and real-time interstitial fluid monitoring, offering valuable insights into disease states and treatment responses. This dual functionality positions HFMNs as a versatile dermatology tool capable of effectively addressing various dermal complications. This review explores the potential use of polymeric biomaterials in HFMN fabrication and their application in treating major dermal disorders, such as acne, psoriasis, and other skin conditions. Furthermore, the review highlights the non-invasive nature of MN-based treatments, underscoring their potential to reduce patient discomfort and improve treatment adherence, as supported by the recent literature.